Active Whale Avoidance by Large Ships: Components and Constraints of a Complementary Approach to Reducing Ship Strike Risk - Gende, Scott M.; Vose, Lawrence; Baken, Jeff; Gabriele, Christine M.; Preston, Rich; Hendrix, A. Noble (Frontiers in Marine Science, 2019)
Lethal ship-whale collisions (‘ship strikes’) constitute a recurring threat to large cetaceans across the globe. Here we describe ‘active whale avoidance’ defined as a mariner making operational decisions to reduce the chance of a collision with a sighted whale. Development and application of a conceptual model of whale avoidance model demonstrated that any activities/operations that increase detection at larger ship-to-whale distances can increase the range of response options for the ship operator, enhancing whale avoidance because (1) the opportunities for detecting a surfacing whale are often limited, (2) the cumulative probability of detecting one of the available ‘cues’ of whale’s presence decreases with increased ship-to-whale distances, and (3) a series of steps must occur before the ship can achieve a new (risk lowering) operational state. Identified options for enhancing whale avoidance include training Lookouts to focus search efforts on a ‘Cone of Conern’, defined here as the area forward of the ship where whales are at risk of collision based on the whale and ship’s transit/swimming speed and direction of travel. Standardizing protocols for rapid communication of relevant sighting information among bridge team members can also increase avoidance by assuring information is of sufficient quality to be ‘actionable’. We also found that, for some marine pilots in Alaska, a slight change in course tends to be preferable to slowing the ship in response to a single sighted whale, owing, in part, to the substantial distance required to achieve an effective speed reduction in a safe manner. Yet, planned, temporary speed reductions in known areas of whale aggregations is commonly practiced, highlighting the value of real-time sharing of whale sighting data by mariners. Finally, development of these concepts in modules in full-mission ship simulators can be of significant value in (a) training inexperienced mariners (2) helping regulators understand the feasibility of avoidance options, and (3) identifying priority research threads. We conclude that application of active whale avoidance techniques by large ships is a feasible yet underdeveloped tool for reducing collision risk globally, and highlight the value of integrating ideas across disciplines to finding solutions to mutually desired conservation outcomes.